Hubungan antara Pengetahuan dan Sikap Masyarakat dengan Perilaku Pencegahan Demam Berdarah Dengue di Wilayah Kerja Puskesmas Tompaso - Momongan, Merry Vike; Niode, Nurdjannah Jane; Katuuk, Mario Esau (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2025)
Background: Dengue Hemorrhagic Fever is an endemic disease in Indonesia, significantly influenced by community prevention behavior. Knowledge and attitudes are the main factors in the low effectiveness of prevention behavior. Objective: This study aims to analyze the relationship between the level of knowledge and attitude of the community with dengue prevention behavior of DHF in the working area of Puskesmas Tompaso. Research Methods: This study used a descriptive design with a cross-sectional approach. A total of 221 respondents was randomly selected using convenience sampling. Data were collected through questionnaires and analyzed using spearman correlation test. Results: There is a significant relationship between knowledge and prevention behavior with a correlation value of r = 0,748 and a p-value = 0,000 and there is a relantionship between attitudes and prevention behavor with a correlation value of r =0 ,889 with a p-value = 0,000. Conclusion: Community knowledge and attitudes contribute to better behavior. The better the knowledge and attitude of the community will affect good behavior as well. Keywords: dengue demorrhagi fever, knowledge, attitudes, prevention behavior